Regulation of the immune CD155–CD226–TIGIT axis by cyclin D-CDK4/6 - Anne Fassl; Miriam Palacios Espinoza; Deborah Butter; Aleksandra Kolodziejczyk; Marco Seehawer; Charlotte Hill; Xiaohan Ning; Timothy B. Branigan; Johany Peñailillo; Charupong Saengboonmee; Heta Jadhav; Krzysztof W. Kotowski; et al. (Proceedings of the National Academy of Sciences, 2026)
Cyclin D-CDK4/6 is a component of mammalian cell-cycle machinery that drives cell proliferation. Small-molecule inhibitors of CDK4/6 have been approved for treatment of breast cancer patients. In addition to halting cell-cycle progression, inhibition of CDK4/6 can affect other tumor cell-intrinsic and -extrinsic functions. Here, we examined the impact of CDK4/6 inhibition on the CD155–CD226–TIGIT pathway that operates at the interface of tumor cells and the immune environment. We demonstrate that inhibition of CDK4/6 upregulates the expression of surface CD155 protein in cancer cells and downregulates an immuno-inhibitory receptor TIGIT in tumor-infiltrating lymphocytes. We observed these effects in human breast cancer cell lines, in mouse mammary carcinoma allograft models, in freshly resected human breast tumors and in paired pre-/on-treatment biopsies of breast cancers from patients undergoing monotherapy with a CDK4/6 inhibitor. We propose that inhibition of CDK4/6, through its tumor cell-intrinsic and -extrinsic effects, may shift the balance from the immunoinhibitory CD155–TIGIT to the immunostimulatory CD155–CD226 interaction, and through this mechanism may augment the antitumor immunity. Our results suggest that coadministration of CDK4/6 inhibitors and anti-TIGIT antibodies may further promote CD155–CD226-signaling and may have a strong synergistic antitumor effect.